2019
DOI: 10.1186/s13017-019-0224-7
|View full text |Cite
|
Sign up to set email alerts
|

2017 WSES and SICG guidelines on acute calcolous cholecystitis in elderly population

Abstract: Background Gallstone disease is very common afflicting 20 million people in the USA. In Europe, the overall incidence of gallstone disease is 18.8% in women and 9.5% in men. The frequency of gallstones related disease increases by age. The elderly population is increasing worldwide. Aim The present guidelines aims to report the results of the World Society of Emergency Surgery (WSES) and Italian Surgical Society for Elderly (SICG) consensus conference on acute calcolous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 95 publications
3
100
0
5
Order By: Relevance
“…Despite the interest in ageing and elderly patients is very high with increasing number of publications about these patients, the concept of "frailty" remains still not clearly defined [98]. Due to a lack of definite criteria and definitions and of well-designed studies in surgical patients with specific including criteria, we decided, according to Pisano et al [99], to adopt a pragmatic definition of an age older than 65 years to define elderly population, according to the job retirement and life expectancy in Italy and western countries; moreover, most of the available studies in literature adopt this definition. The great limitation of this definition is obvious and clear: age alone could not define the frailty of a patient and patients with the same age could be very different for comorbidity and performance status.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the interest in ageing and elderly patients is very high with increasing number of publications about these patients, the concept of "frailty" remains still not clearly defined [98]. Due to a lack of definite criteria and definitions and of well-designed studies in surgical patients with specific including criteria, we decided, according to Pisano et al [99], to adopt a pragmatic definition of an age older than 65 years to define elderly population, according to the job retirement and life expectancy in Italy and western countries; moreover, most of the available studies in literature adopt this definition. The great limitation of this definition is obvious and clear: age alone could not define the frailty of a patient and patients with the same age could be very different for comorbidity and performance status.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus highly relevant to develop the most appropriate care measures and to guide patient-centered decision-making around emergent care [22]. ACCBD is a relatively-frequent diagnosis in patients over 65 years, and while some consensus guidance exists, age is not considered to be a contraindication to operative management [2].…”
Section: Discussionmentioning
confidence: 99%
“…Snapshot audit, a form of prospective, observational, non-randomised multi-centre cohort study, is a novel methodology for prospective collaborative cohort studies that has allowed detailed, de ned datasets to be accrued in line with a priori analyses stated in pre-publication, open access protocols led with clinical trial repositories [2][3][4] . This methodology, which is superior in some respects to large retrospective registries, has been recently embraced by surgeons as a pragmatic alternative to randomized controlled trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the guideline forwarded by Pisano, laparoscopic cholecystectomy should be considered for all; the age, on its own, is not a contraindication for surgery (Pisano et al 2019). While Nassar in his study found that age of the patient is a significant factor determining the likelihood of death and the length of hospital stay after any type of procedure of gallstones removal (Nassar & Richter 2019).…”
Section: Discussionmentioning
confidence: 99%